Dreams Die First : A novel - Robbins, Harold, 1916-1997 (New York Simon and Schuster, 1978)
"Tells the tale of a loner who rises to the top only to discover that fame has its consequences"
Keywords: Publishers and publishing -- California--Los Angeles